If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.25(3x + -8) = 2(0.5x + 4) Reorder the terms: 0.25(-8 + 3x) = 2(0.5x + 4) (-8 * 0.25 + 3x * 0.25) = 2(0.5x + 4) (-2 + 0.75x) = 2(0.5x + 4) Reorder the terms: -2 + 0.75x = 2(4 + 0.5x) -2 + 0.75x = (4 * 2 + 0.5x * 2) -2 + 0.75x = (8 + 1x) Solving -2 + 0.75x = 8 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 0.75x + -1x = 8 + 1x + -1x Combine like terms: 0.75x + -1x = -0.25x -2 + -0.25x = 8 + 1x + -1x Combine like terms: 1x + -1x = 0 -2 + -0.25x = 8 + 0 -2 + -0.25x = 8 Add '2' to each side of the equation. -2 + 2 + -0.25x = 8 + 2 Combine like terms: -2 + 2 = 0 0 + -0.25x = 8 + 2 -0.25x = 8 + 2 Combine like terms: 8 + 2 = 10 -0.25x = 10 Divide each side by '-0.25'. x = -40 Simplifying x = -40
| 490000000=119x-237516 | | x+6y=50 | | 3x^2+7x=3x+-20 | | .8x-8=2.3x-17 | | 5(-2x-4)=-16 | | y=2x+22000 | | 2x+3+x= | | 4x+5x=2x-11 | | 15x-19x= | | 3x^2+7x=3x-20 | | 2x-23+23=87+23 | | (8x^2-5x^3)-(6x^2-9x^3)= | | 3y^2=-11y+20 | | -3(5t-2)+4t=6t-2 | | 6c-10c+13c-7= | | 5y^2=-3y+14 | | p-4=-g+p | | 4cos^2x+4cosx+1=0 | | -3(x+8)-43=5-54 | | (19X/3)/(44Y/3) | | -4(x+5)-44=8-36 | | 15Y-Y/3 | | Y=(2)x+b | | 5-4tanx=8 | | 8n=26 | | 560=4x+8(20) | | 7X-2X/3 | | -0.10(83)+0.60x=0.05(x-12) | | 34y+32=24y-3 | | -4-2y/5=-12 | | 6/5(5-4c)=-18 | | 2(x+9)=-6x+2 |